Influence of Product Packaging Quality and Delivery Time on Consumer Satisfaction PT J&T Express Agent DKI Jakarta East Jakarta Region - Aprianto, Vito Rimbo; Habibie, Fajar; Haris, Haris; Ozali, Imam (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2023)
This study aims to determine the effect of product packaging quality and delivery time on the consumer satisfaction of PT. J&T Express agent DKI Jakarta in the East Jakarta area. The population in this study is 300,000 consumers of J&T agent DKI Jakarta in the East Jakarta area, with a sample of 100 consumers based on the Slovin formula and use the random sampling. This study uses primary data with data collection methods through questionnaires distributed to 100 respondents. Data analysis technique using multiple linear regression analysis and using the SPSS version 26.0 program. The results show that the quality of packaging has a positive and significant effect on consumer satisfaction, with a regression coefficient 0.405 and a significant value of 0.000. Ontime delivery has a positive and significant effect on consumer satisfaction with a regression coefficient value of 0.437 and a significant 0.000.